SERO-PREVALENCE OF LEPTOSPIROSIS IN SMALL RUMINANTS IN PUDUKKOTTAI DISTRICT OF TAMIL NADU - Paramsivam, A; Jagatheesan, PN Richard; Reetha, T Luthu; Henry, A Clemant Ebenezer (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A study was conducted to document sero prevalence level of leptospiral serovars in small ruminants in Pudukkottai district of Tamil Nadu by subjecting the serum samples to MAT. The results indicated that sero positivity rate in sheep and goat was18.35 per cent and 12.87 per cent respectively. The predominant leptospiral serovar pomona and grippotyphosa was found in sheep and canicola in goats.